Susceptibility of different breeds of goats in Kenya to experiment infection with Trypanosoma congolense - Whitelaw, D.D.; Kaaya, G.P.; Moulton, J.E.; Moloo, S.K.; Murray, M. (Springer, 1985)
A study conducted to assess whether there was any evidence of genetic resistance to African trypanosomiasis in different goat breeds including East African, Galla and Crossbreds between East African and Galla, Nubian or Toggenburg.